Growth of Different Zinc Oxide Nanostructures under Hydrothermal pH Values - Saja A. H. Abbas; Ehssan S. Hassan; Oday M. Abdulmunem (مجلة بغداد للعلوم)
Flower- and rod-like nanostructures of zinc oxide were prepared by the hydrothermal method at 90°C for three hours. Three 0.028 molar solutions, with pH values of 9, 10, and 11, were deposited on glass substrate/ZnO seed layers. All the prepared samples had a polycrystalline diffraction pattern with dominant diffraction from the (002) plane. With increasing pH, the crystallite size increased to a maximum of 37.6 nm. The importance of the research lies in the growth of different nanostructures of zinc oxide by controlling the degree of pH, as the results showed the emergence of flower structures ZnO NFs at pH 11 with a particle size of 100-800 nm, and the development of nanostructures in the form of a bundle of rods at pH 10 with a particle size of 500-800 nm and the development of ZnO NRs in the form of solitary rods perpendicular to the surface at pH 9, with a grain size of 70-80 nm. The optical properties showed a decrease from 78.75% to 79.32% as the pH was increased from 9 to 11, and the value of the energy gap increased from 3.18 eV to 3.31 eV with the increase in the pH value from 9 to 11.